Cisticercose bovina: dados epidemiológicos da região nordeste do Rio Grande do Sul e material educativo - Brum, Jerônimo Gonçalves da Silva (My University, 2022)
Cysticercosis is a disease that have cattle as the intermediate hosts of Taenia saginata. This parasitic disease is responsible for losses of large financial sums in the meat production chain. Due to the fact that it is a zoonosis, both veterinary and human medicine are involved in the prevention and treatment of the disease. Thus, the objective of this study was to analyze the situation of bovine cysticercosis in the Northeast region of Rio Grande do Sul, in addition to carrying out a survey on the profile of fiscal veterinarians who work in the region and producing an educational material. From June to July 2020, a questionnaire was applied to tax Veterinarians on sanitary inspection and the taeniasis-cysticercosis complex to assess their knowledge on the subject. Data for the years 2015 to 2019 were collected and statistically analyzed from cattle sent for slaughter from the municipalities of Serra Gaúcha and Campos de Cima da Serra, data from cattle slaughtered in regional slaughterhouses and the sites of insertion of the parasite in the carcass. As a way of promoting knowledge about the disease, educational material was produced. The epidemiological survey resulted in an occurrence of 1,10% of cysticercosis in slaughtered cattle from the municipalities of the two regions studied. In regional refrigeration plants, the observed occurrence was 0,95%. The observation of cysticerci in the sites was 68.8% in the heart, 17.6% in the head, 5.9% in the liver, 2.7% in the carcass, 2.5% in the diaphragm, 2.2% in the tongue and 0.03% in the esophagus. The information obtained through the study shows that cysticercosis is present in the region in expressive values, which demands sanitary education measures for humans, management directed to cattle and rigorous inspection of carcasses, thus causing the incidence of the disease to be really reduced. [resumo fornecido pelo autor]
A cisticercose, enfermidade inerente aos bovinos, hospedeiros intermediários da Taenia saginata, é responsável por prejuízos de grandes somas financeiras na cadeia produtiva da carne. Devido ao fato de tratar-se de uma zoonose, tanto na medicina veterinária quanto na medicina humana estão envolvidas na prevenção e tratamento da enfermidade. Assim, o objetivo deste estudo foi analisar a situação da cisticercose bovina na região Nordeste do Rio Grande do Sul, além de realizar um levantamento sobre o perfil dos médicos veterinários fiscais que atuam na região e produzir um material educativo. No período de junho a julho de 2020 foi aplicado um questionário virtual dirigido a médicos veterinários fiscais sobre inspeção sanitária e o complexo teníase-cisticercose para avaliar o conhecimento acerca do assunto. Foram coletados e analisados estatisticamente dados referentes aos anos de 2015 a 2019 dos bovinos enviados para abate oriundos dos municípios da Serra Gaúcha e Campos de Cima da Serra, dados dos bovinos abatidos em frigoríficos regionais e os sítios de inserção do parasita na carcaça. Como forma de promover o conhecimento sobre a enfermidade, foi produzido material educativo. O levantamento epidemiológico resultou em uma ocorrência de 1,10% de cisticercose nos bovinos abatidos provenientes dos municípios das duas regiões estudadas. Nas plantas frigoríficas regionais, a ocorrência observada foi de 0,95%. A observação de cisticercos nos sítios foi de 68,8% no coração, 17,6% na cabeça, 5,9% no fígado, 2,7% na carcaça, 2,5% no diafragma, 2,2% na língua e 0,03% no esôfago. As informações obtidas através do estudo mostram que a cisticercose se encontra presente na região em valores expressivos, o que demanda medidas de educação sanitária para humanos, manejos direcionados aos bovinos e inspeção rigorosa de carcaças, fazendo assim com que a incidência da doença seja realmente diminuída. [resumo fornecido pelo autor]
Keywords: Bovino - Doenças; Bovinos - Parasitos; Zoonoses; Cattle - Diseases; Cattle - Parasites; Zoonoses